The Azerbaijani Adaptation of the Utrecht Work Engagement Scale: Investigating Its Influence on Psychological Distress and Life-Job Satisfaction - Nahmatova, Ulviyya; Aliyeva, Matanat; Rustamova, Narinj; Zalova Nuriyeva, Ulkar; Rustamov, Elnur (Technium Social Sciences Journal, 2024)
Teacher well-being plays a vital role in fostering a positive and productive learning environment, as it directly impacts both their professional performance and the overall success of their students. Consequently, this study aimed to adapt the Utrecht Work Engagement Scale for use among Azerbaijani school principals and to investigate the relationships between work and wellbeing, psychological distress, and life-job satisfaction. Data were gathered from 976 Azerbaijani school principals. The adaptation process involved confirmatory factor analysis, evaluations of criterion-related validity, and reliability testing. Additionally, the relationships between work and wellbeing, psychological distress, and life-job satisfaction were examined through mediational analysis. The confirmatory factor analysis revealed that the questionnaire consisted of 17 items, highlighted three factors, and demonstrated an acceptable model fit. The scale showed satisfactory reliability coefficients for both its individual factors and the overall score. Moreover, the results indicated that work and wellbeing was positively correlated with life-job satisfaction and negatively associated with psychological distress. Lastly, the findings revealed that psychological distress mediated the relationship between work and wellbeing and life-job satisfaction. These outcomes suggest that the Azerbaijani version of the Utrecht Work Engagement Scale possesses strong psychometric properties.